A survey study on antibiotic prescription practices for acute asthma exacerbations: An European academy of allergy and clinical immunology task force report - Anne‐Lotte Redel; Wojciech Feleszko; Alessandra Arcolaci; Francesca Cefaloni; Marina Atanaskovic‐Markovic; Gert‐Jan Braunstahl; Cristina Boccabella; Matteo Bonini; Aspasia Karavelia; Eefje Louwers; Norbert Mülleneisen; Liam O'Mahony; et al. (Clinical and Translational Allergy, 2024)
Abstract Introduction Guidelines recommend treating asthma exacerbations (AAEs) with bronchodilators combined with inhaled and/or systemic corticosteroids. Indications for antibiotic prescriptions for AAEs are usually not incorporated although the literature shows antibiotics are frequently prescribed. Aim To investigate the antibiotic prescription rates in AAEs and explore the possible determining factors of those practices. Methods A digital survey was created to determine the antibiotic prescription rates in AAEs and the influencing factors for the prescription practices. The survey was distributed among European academy of allergy and clinical immunology (EAACI) members by mass emailing and through regional/national societies in the Netherlands, Italy, Greece, and Poland. Furthermore, we retrieved local antibiotic prescription rates. Results In total, 252 participants completed the survey. Respondents stated that there is a lack of guidelines to prescribe antibiotics in AAEs. The median antibiotic prescription rate in this study was 19% [IQR: 0%–40%] and was significantly different between 4 professions: paediatrics 0% [IQR: 0%–37%], pulmonologists 25% [IQR: 10%–50%], general practitioners 25% [IQR: 0%–50%], and allergologists 17% [IQR: 0%–33%]) (p = 0.046). Additional diagnostic tests were performed in 71.4% of patients before prescription and the most common antibiotic classes prescribed were macrolides (46.0%) and penicillin (42.9%). Important clinical factors for health care providers to prescribe antibiotics were colorised/purulent sputum, abnormal lung sounds during auscultation, fever, and presence of comorbidities. Conclusion In 19% of patients with AAEs, antibiotics were prescribed in various classes with a broad range among different subspecialities. This study stresses the urgency to compose evidence‐based guidelines to aim for more rational antibiotic prescriptions for AAE.